Vitamin D Deficiency in Vitiligo: A Cross-Sectional Analysis of Prevalence and Predictors - Syed Bilal Ahmed, Sajida Jabeen, Asadullah Khan, Neelam Ayub (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vitamin D deficiency is a global health issue and has been implicated in autoimmune and pigmentary disorders, including vitiligo. However, prevalence estimates and associations with disease severity remain inconsistent. Objective: To assess the frequency and severity of vitamin D deficiency among vitiligo patients and to evaluate demographic and clinical predictors. Methods: This cross-sectional study included 165 vitiligo patients attending dermatology clinic from Dec 2022 to May 2023. Serum 25-hydroxyvitamin D [25(OH)D] was measured using chemiluminescent immunoassay and categorized as deficient (<20 ng/mL), insufficient (20–29 ng/mL), or sufficient (≥30 ng/mL). Demographic and clinical data were recorded. Logistic regression was applied to identify independent predictors of vitamin D deficiency. Results: Of 165 patients (mean age 34.2 ± 11.5 years; 59.4% female), 23.0% were deficient, 38.8% insufficient, and 38.2% sufficient. Female sex, indoor occupation, and winter recruitment were significantly associated with deficiency (p<0.05). Multivariate logistic regression showed that indoor occupation (OR 2.45, 95% CI 1.11–5.40, p=0.027) and winter season (OR 2.12, 95% CI 1.01–4.47, p=0.046) independently predicted deficiency. No significant association was observed between vitamin D status and vitiligo severity index. Conclusion: Vitamin D deficiency and insufficiency affect nearly two-thirds of vitiligo patients. Risk is highest in women, indoor workers, and those recruited in winter, but serum vitamin D was not associated with disease severity. Screening and preventive measures may be warranted in high-risk groups. Keywords: Vitiligo, Vitamin D deficiency, Frequency, Logistic regression, Risk factors